Pencarian Data Barang Produk Atribut Sekolah Menggunakan Algoritma Binary Search - Risma Dara Awal Aviantika; Kustanto Kustanto; Muhammad Hasbi (Jurnal Teknologi Informasi dan Komunikasi (TIKomSiN), 2021)
Technology and information that is growing and sophisticated must be balanced according to the needs. For it was made the application of binary algorithms for the search data goods production of school attributes. Many methods in search with the goal of making it easier to search, e.g. search data of production items of school attributes with binary search method. Convection in the search of production goods using the manual way by looking for the archive data written in the notebook, the purpose of this research is to create a data retrieval system of goods that will be applied as a data retrieval tool of goods, as well as change the system manual to the computing system. In this research using Binary Search algorithm. Binary search algorithm is a technique applied only on the sorted element (sorted). This research using method of binary search algorithm with analysis stage, system design, coding/construction, testing, and implementation. In the analysis stage, the collection of data conducted is observation and literature study. At the system design stage using Unified Modelling Language (UML) include the use case diagram, activity diagram, Sequence diagram, and Diagram class. At the construction stage using the Java programming language using Netbeans and MySQL Server tools while the implementation of this system is the application of data retrieval of goods. To know the eligibility of a system, it is necessary to test against the search time of 210 data each time duration, 0.0004 seconds, 0.0005 seconds, 0.0006 seconds, 0.0007 seconds, 0.0008 seconds, 0.0009 seconds, 0.0010 seconds, 0.0012 seconds, 0.0014 seconds, 0.00117 seconds. The final result of this study is the application of search for production goods with Binary Search Algorithm Method.